A longitudinal course pilot to improve surgical resident acquisition of quality improvement skills - Ahuja, Vanita (PLoS One, 2021)
PROBLEM: Despite mounting evidence that incorporation of QI curricula into surgical trainee education improves morbidity and outcomes, surgery training programs lack standardized QI curricula and tools to measure QI knowledge. In the current study, we developed, implemented, and evaluated a quality improvement curriculum for surgical residents. INTERVENTION: Surgical trainees participated in a longitudinal, year-long (2019–2020) curriculum based on the Institute for Healthcare Improvement’s online program. Online curriculum was supplemented with in person didactics and small group projects. Acquisition of skills was assessed pre- and post- course via self-report on a Likert scale as well as the Quality Improvement Knowledge Application Tool (QIKAT). Self-efficacy scores were assessed using the General Self-Efficacy Scale. 9 out of 18 total course participants completed the post course survey. This first course cohort was analyzed as a pilot for future work. CONTEXT: The project was developed and deployed among surgical residents during their research/lab year. Teams of surgical residents were partnered with a faculty project mentor, as well as non-physician teammates for project work. IMPACT: Participation in the QI course significantly increased skills related to studying the process (p = 0.0463), making changes in a system (p = 0.0167), identifying whether a change leads to an improvement (p = 0.0039), using small cycles of change (p = 0.0000), identifying best practices and comparing them to local practices (p = 0.0020), using PDSA model as a systematic framework for trial and learning (p = 0.0004), identifying how data is linked to specific processes (p = 0.0488), and building the next improvement cycle upon success or failure (p = 0.0316). There was also a significant improvement in aim (p = 0.037) and change (p = 0.029) responses to one QIKAT vignette. LESSONS LEARNED: We describe the effectiveness of a pilot longitudinal, multi component QI course based on the IHI online curriculum in improving surgical trainee knowledge and use of key QI skills.